Analisis Implementasi Kebijakan Kurikulum Merdeka Berdasarkan Teori Edward III di Tingkat Sekolah Dasar Kabupaten Luwu Utara - Septiani, Elya (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research aims to analyze the implementation of the independent curriculum policy based on Edward III’s theory at the elementary school level in North Luwu Regency. The research method uses qualitative methods with a phenomenological type. Data collection through observation, interviews and documentation. The technique for collecting informants uses a purposive sampling method, namely; North Luwu Regency Education Office, school principals, teachers and students. The research results based on Edward III’s theory are; Communication is carried out by coordinating in the form of outreach activities by the government sector to schools, involving school principals, teachers, students and parents, human resources supported by teachers and school staff, then facility resources supported by the existence of an independent teaching platform, as well as human resources funds obtained from school operational assistance funds (BOS), disposition, demonstrated by conducting teacher training in making independent curriculum teaching modules (prototypes) and KKG activities, bureaucratic structure, direction to school principals and teachers to continue learning and conducting training on the independent platform Study. The conclusion is that the implementation of the independent curriculum has gone well at the elementary school level in North Luwu Regency.